At least three human homeoboxes on chromosome 12 belong to the same transcription unit. - Simeone, A (1988)
Mammalian homeoboxes show a clustered chromosomal organization. In the mouse, at least seven homeoboxes on chromosome 6 and at least six on chromosome 11 identify the murine Hox-1 and Hox-2 loci, respectively. A number of homeoboxes on chromosome 7 define the human HOX-1 locus and homeoboxes on chromosome 17 define the human HOX-2 locus. We studied the genomic organization of three homeobox sequences of the HOX-3 locus on chromosome 12 and analyzed transcripts from this region. Structural characterization and sequencing of several cDNA clones reveal that the three homeobox sequences present in this chromosomal region identify a single transcription unit. Primary transcripts are alternatively processed to give mature messengers with a common 5' noncoding exon encoding different proteins containing one of the three homeodomains.